DINAMIKA PENGAWASAN PEMILIHAN GUBERNUR DAN WAKIL GUBERNUR RIAU TAHUN 2018 - Ary Dwi Rahmat; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The election of the Governor and Deputy Governor is an embodiment of a democratic country. Indonesia, which is a democracy, conducts Regional Elections every 5 years. In the Election of the Governor and Deputy Governor, of course, it will be alleviated fairly and clean from violations or fraud, in this case Bawaslu as the highest body in the supervision of elections must act optimally in order to create an election that is clean from violations, but in reality there are still violations and fraud encountered by Bawaslu. This happens because of the lack of maximum and there are several obstacles in the supervision carried out by Bawaslu. The formulation of the problem in this study is How Dynamics of Supervision of the Election of the Governor and Deputy Governor of Riau in 2018 and What are the Obstacles in Supervision of the Election of the Governor and Deputy Governor of Riau in 2018. The purpose of this study is to find out How Dynamics of the Election of Governor and Deputy Governor of Riau in 2018 and What are the Obstacles in Supervision of the Election of the Governor and Deputy Governor of Riau in 2018. Theories used according to Donnelly (1996). In collecting data the author uses interview and documentation techniques. The results of the author's research are the Supervision of the Election of the Governor and Deputy Governor of Riau in 2018 which has not been carried out maximally because there are findings of violations. The obstacles in this supervision are the Budget and the number of supervisory personnel, political culture and the lack of public knowledge about the Regional Head Election itself. Keywords: Oversight, Election of Governor and Deputy Governor.